Revised fast convolution - Pupeikis, Rimantas (Lietuvos matematikos rinkinys, 2016)
It is assumed that linear time-invariant (LTI) system input signal samples are updated by a sensor in real time. It is urgent for every new input sample or for small part of new samples to update a convolution as well. The idea is that fast Fourier transform (FFT) algorithm, used to calculate output frequency samples (f.s.), should not be recalculated with every new input sample. It is needed just to modify the convolution algorithm, when the new input sample replaces the old one. An example of computation of the convolution with ordinary and modified 8-point Fourier code matrix is presented.